The Toys' Party - Hunt, Roderick and Brychta, Alex (Oxford University Press, 2017)
The Stage 2 Biff, Chip and Kipper Stories provide a rich story context to help develop language comprehension and decoding skills. Stories, More Stories A and More Stories B offer a predictable sentence structure to support reading success.
Include Illustrations